Total tannin levels analysis of brown algae (sargassum sp and padina sp) to prevent blood loss in a surgery - Abul Fauzi; Satriani Lamma; Muhammad Ruslin (DiscoverSys Inc., 2018)
Objective: Tooth extraction in oral surgery may cause complications such as bleeding. A ttannin is an astringent group that can accelerate the process of bleeding cessation by precipitating the blood protein, specifically thrombin. One of the plants containing tannin is brown algae. The total tannin level in brown algae, specifically Sargassum sp. and Padina sp., will be determined.Material and Methods: This research is an experimental research using post-test only with control group design. The seaweed used in this study was taken from the waters of Punaga, Takalar. The dried seaweed was subsequently extracted using maceration. Extracts were diluted using ethanol and. then was reacted with 7.5% Folin and 1% NaOH. The measurement of tannin level was performed using a standard curve of tannic acid.Results: Total tannin level of Sargassum sp. was 0.5152 Â± 0.9634 %, while the total tannin level of Padina sp. was 1.1321 Â± 0.09747 %.Conclusion: Padina sp. has a higher total tannin level than Sargassum sp.Â